1977
DOI: 10.1002/cne.901710302
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic projections of the superior colliculus in the rhesus monkey, Macaca mulatta. A light and electron microscopic study

Abstract: The projections of the superior colliculus to the thalamus have been studied in the monkey, Macaca mulatta, with anterograde degeneration techniques. The superior colliculus has been shown to project to the inferior nucleus of the pulvinar in a topographical manner with the lower visual field represented dorsomedially and the upper field ventrolaterally. The peripheral zone is located along the medial border and the fovea at the dorsolateral angle adjacent to the lateral geniculate nucleus. The superior collic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(56 citation statements)
references
References 62 publications
4
52
0
Order By: Relevance
“…Input from V2 may also reach the pulvinar complex through superior colliculus-pulvinar projections (Benevento and Fallon, 1975;Partlow et al, 1977;Harting et al, 1980;Benevento and Standage, 1983). Tectal-recipient regions in the pulvinar appear to overlap with cortically projecting regions (Benevento and Rezak, 1976), but the specificity of the tectopulvinofugal projections with respect to thick and thin stripes in V2 and with other visual areas of the dorsal or ventral streams remains to be determined.…”
Section: Segregation Of V2 Subcortical Loopsmentioning
confidence: 92%
“…Input from V2 may also reach the pulvinar complex through superior colliculus-pulvinar projections (Benevento and Fallon, 1975;Partlow et al, 1977;Harting et al, 1980;Benevento and Standage, 1983). Tectal-recipient regions in the pulvinar appear to overlap with cortically projecting regions (Benevento and Rezak, 1976), but the specificity of the tectopulvinofugal projections with respect to thick and thin stripes in V2 and with other visual areas of the dorsal or ventral streams remains to be determined.…”
Section: Segregation Of V2 Subcortical Loopsmentioning
confidence: 92%
“…The inferior pulvinar nucleus also contains populations of cells projecting to more than one cortical area, including superficial layers Rezak, 1975, 1976;Ogren and Hendrickson, 1977;Rezak and Benevento, 1979;Lund et al, 1981;Lysakowski et al, 1988;Cusick et al, 1993). Inputs to both the S laminar and interlaminar cells and the inferior pulvinar nucleus arise in the superficial layers of the superior colliculus (Benevento and Fallon, 1975;Partlow et al, 1977;Harting et al, 1978Harting et al, , 1991 and both receive inputs from the retina (a restricted area adjacent to the lateral geniculate in the case of the inferior pulvinar nucleus) (Campos-Ortega et al, 1972;Tigges et al, 1977;Hendrickson et al, 1970;Kaas et al, 1978;Tokunaga et al, 1981). The parallel with the diffusely projecting matrix of the ventral thalamic nuclei seems clear (see also Diamond et al, 1993, andCusick et al, 1993).…”
Section: Specific and Unspecific Expression Of Camkii Isoforms In Relmentioning
confidence: 99%
“…Anatomic studies have shown that the P 1 and P 2 fields have connections with V1, V2, V4, and MT (CamposOrtega and Hayhow, 1972;Benevento and Rezak, 1976;Ogren and Hendrickson, 1976;Benevento and Davis, 1977;Graham, 1982;Maunsell and Van Essen, 1983;Standage and Benevento, 1983;Ungerleider et al, 1983Ungerleider et al, , 1984Cusick et al, 1993;Gutierrez and Cusick, 1997), and both receive inputs from the superficial layers of the superior colliculus (Benevento and Fallon, 1975;Partlow et al, 1977;Harting et al, 1980;Benevento and Standage, 1983;Stepniewska et al, 1999). The P 3 field has connections with MT, MST, and FST (Maunsell and Van Essen, 1983;Standage and Benevento, 1983;Ungerleider et al, 1984;Boussaoud et al, 1992).…”
mentioning
confidence: 97%